Adolescents' Utilization of a Tertiary-Level Pediatric Emergency Department in Italy - Cozzi, Giorgio; Passaglia, Lisa; Agrusti, Anna; Giangreco, Manuela; Giorgi, Rita; Barbi, Egidio (Frontiers in Pediatrics, 2022)
Aim: Describe the use of the emergency department of a tertiary-level children’s hospital in Italy by adolescents. Methods: This retrospective study was based on the medical records of patients aged 13 to 17 years, who accessed the emergency department of the Institute for Maternal and Child Health of Trieste, from 1 January to 31 December 2018. The primary outcome was to describe the leading causes of access, diagnoses, rate of hospitalization, and ward of destination among adolescent patients. Results: During the study period, 24599 patients accessed the department. Among them, 3062 were adolescents, for a total of 3895 unscheduled visits. The principal causes of access were trauma (45.3%) and organic diseases (38.8%). 249 adolescents (6.4%) had mental health problems. 142 adolescents (3.6%) were admitted to the hospital, 54 of whom (38%) to the neuropsychiatric ward, for mental health problems. Conclusions: Among adolescents seen in this Italian tertiary-level children’s hospital, mental health problems represented a small proportion of emergency department visits but were the leading cause of urgent hospitalization.